The effects of the World Heritage listing of Al Ain archaeological sites on the protection and management of these site - Al Kaabi, Abdulla; Musa, Majd (Al-Adab Journal, 2025)
This study highlights the impact of inscribing archaeological sites in Al Ain, UAE, on the World Heritage List. Focusing particularly on the Al Ain Oasis as a case study, it aims to demonstrate the significant improvements that have occurred at the site in various areas, including protection, preservation, and the development of the oasis as a cultural tourism destination. The study discusses the role of key partners in managing these sites, detailing their roles and responsibilities and how the local community has been integrated as an active part of the management system. The study details the methods employed in the management and maintenance of Al Ain archaeological sites, noting the challenges faced and the strategies adopted to overcome them and emphasizing the importance of teamwork and ongoing collaboration between government entities and the local community. The study highlights the positive transformations that the historical sites in Al Ain have undergone following their inscription on the World Heritage List, demonstrating how this has enhanced local identity and improved the infrastructure of the sites, leading to economic opportunities and encouraging tourism. Inscription on the World Heritage List was a pivotal step in bolstering efforts to preserve cultural and natural heritage, as it helped raise awareness and improve the efforts directed toward the conservation of these sites. The study also highlights how legislation, laws, and control mechanisms have been established to strengthen the efforts to protect the sites from potential threats. It shows how several historical buildings have been repurposed and developed as cultural destinations that serve the local community and highlight the exceptional value of the sites. The study provides detailed recommendations aimed at improving the strategies for preserving world heritage and promoting sustainable cultural and tourist development in Al Ain. It emphasizes the importance of continuous investment in cultural and natural heritage and the need to adopt a comprehensive approach that includes all stakeholders to ensure a prosperous future for the management of cultural sites. Thus, the study contributes to enriching knowledge about world heritage protection and provides a valuable framework for advancing cultural and tourism development.